A Global Strategy for Building Clinical Capacity and Advancing Research in the Context of Malnutrition and Cancer in Children within Low- and Middle-Income Countries. Issue 54 (11th September 2019) - Ladas, Elena J; Gunter, Marc; Huybrechts, Inge; Barr, Ronald
Abstract: Cancer is one of the prominent noncommunicable diseases and is responsible for more than 8 million deaths each year worldwide. It is expected to impact up to 22 million people annually by 2030, and more than 60% of new patient cases will be in Asia, Africa, and Central and South America. Despite improvements in the delivery of care to children in low- and middle-income countries, survival of those with cancer is as low as 10%; a figure that is in stark contrast to overall childhood cancer survival rates in North America and Western Europe. Although many factors are contributing to this disparity, access to well-educated health-care workers, knowledgeable in both antineoplastic and supportive care, particularly nutritional assessment and therapy, is necessary for effective treatment and reduced morbidities of children with cancer. To this end, we identify approaches for advancing nutritional care such as building nutritional capacity and education as well as advancing rigorous nutritional science through the establishment of multicountry research groups among pediatric oncology units located in low- and middle-income countries.